The vibrational signatures of polyaromatic hydrocarbons on an ice surface. Issue Volume 15:Issue S350(2019) (April 2019) - Clark, Victoria H.J.; Benoit, David M.
Abstract: We use quantum chemical techniques to model the vibrational spectra of small aromatic molecules on a proton-ordered hexagonal crystalline water ice (XIh) model. We achieve a good agreement with experimental data by accounting for vibrational anharmonicity and correcting the potential energy landscape for known failures of density functional theory. A standard harmonic description of the vibrational spectra only leads to a broad qualitative agreement.